Short-Term Complications After Laparoscopic Choledochal Cyst Radical Surgery: Prevention and Treatment - Zheng, Jiachen; Li, Zhihan; Ye, Yonqin; Wang, Bin (Frontiers in Surgery, 2020)
Background: Shenzhen Children’s Hospital is one of the first hospitals in mainland China to conduct the laparoscopic choledochal cyst radical surgery. We aimed to analyze the short-term complications of treating choledochal cyst with laparoscopic surgery and to provide recommendations to reduce complications. Methods: A retrospective study was carried out from May 2010 to December 2017. The treatment process (preoperative preparation, surgical procedures, and treatment of the short-term complications), age at surgery, the length of surgery, and the length of stay were reviewed and analyzed. Results: A total of 325 cases were included in this study. 4 cases (1.2%) were converted to laparotomy. 23 cases (7.1%) exhibited the short-term complications, including bile leakage occurred in 9 cases (2.8%), chylous ascites in 1 case (0.3%), pancreatic fistula in 2 cases (0.6%), intestinal necrosis in 1 case (0.3%), hemorrhage in 4 cases (1.2%), internal hernia in 2 cases (0.6%), and stoma necrosis in 4 cases (1.2%). Among patients younger than 3 months old, 2 cases (10.5%, P＜0.05) were converted to laparotomy, and 4 cases (21.1%, P＜0.05) exhibited complications. These patients also had a longer operative time (204.9±10.8 min, P＜0.05) and hospital stay (12.2±0.7 d, P＜0.001). Conclusion: In our study, the incidence of short-term complication after laparoscopic choledochal cyst radical surgery was relatively low. This procedure is a quite safe and effective for most patients, even for young children. However, patients younger than 3 months old may require extra attention during the treatment.